A review of the Elachista subula Parenti species complex (Lepidoptera, Elachistidae), with descriptions of nine new Palearctic species - Kaila, Lauri; Nupponen, Kari (Zootaxa, 2018)
Taxonomy of the here established Elachista subula species complex is reviewed. This species complex is subordinate to the E. dispilella group sensu Kaila et al. (2015), in subgenus Aphelosetia. The E. subula species complex is exclusively Palearctic. Most of the currently recognized species occur in dry areas in Central Asia where they appear to form a significant part of the Elachista diversity. The constituent species are characterized by a phallus with bent and sharp-tipped apex, and the vesica with one weakly sclerotized plate-like cornutus that usually bears one blunt or spine-like tooth. Fourteen species are recognized, of which the following 9 are described as new: E. ameteria Kaila, sp. nov. (Type locality country Kazakhstan), E. cisoria Kaila, sp. nov. (Spain), E. cultella Kaila, sp. nov. (Mongolia), E. drepanella Kaila, sp. nov. (Russia: Tuva), E. marusiki Kaila, sp. nov. (Mongolia), E. perona Kaila, sp. nov. (Kyrgyzstan), E. platamodes Kaila, sp. nov. (Croatia), E. scalpra Kaila, sp. nov. (Turkey) and E. spinipyra Kaila, sp. nov. (Turkmenistan). Redescriptions are given to E. mus Parenti¸ E. bimaculata Parenti, E. semnani Parenti, E. subula Parenti and E. acutella Kaila.